Implementation of the Case Method Learning Model in Civics Learning to Improve Critical Thinking Skills of 5th Grade Students at SDN Inpres Padende - Virdania; Umar; Fuaddudin (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to determine the application of the case method learning model in Civics learning to improve critical thinking skills of fifth-grade students at SDN Inpres Padende. This type of research is Classroom Action Research. The results of the study concluded that the average evaluation result for cycle I was 81 with a classical completion percentage of 58%. Meanwhile, the average evaluation result for cycle II was 89, with a classical completion rate of 92%. This means the ideal classical completion target of 85 has been achieved. The percentage increase from cycle I to cycle II was 34%. Improvements can also be seen from the results of the teacher activity observation sheet in cycle I, namely 74% with a category of being implemented quite well and increasing in cycle II to 89% and categorized as being implemented well. The percentage increase from cycle I to cycle II was 15%. Based on the conclusions obtained, to improve the case study learning model, the researcher suggests that teachers innovate in implementing the learning process. The choice of learning method must be tailored to the characteristics of the material and student abilities. Teachers can develop methods that support the implementation of learning. Careful planning makes learning effective and efficient, thereby achieving learning objectives. With a more engaging learning method, it will help students learn and understand the material, one of which is by using the case study learning model.